O papel do estado no combate à pobreza: um estudo de caso do programa bolsa família - Sales, Tainah Simões (2013)
This study aims to analyze the role of the state in combating poverty. We defend the welfare state model because, despite criticism that can be made and its shortcomings, it is the model that is more efficient in resolving social issues and reducing the negative impacts of capitalism, by concerning with the basic conditions of life for all individuals. Moreover, this work aimed studies about the concepts of poverty, concluding in favor of a broad concept, besides the criteria based only on income, which can reflect the real social needs and taking into account individuals' freedoms and equal opportunities for all. Were also objects of study topics related to inequality, minimum existential, social changes and public policies. As a case study, we have chosen the analysis of the Bolsa Família Program, which this year celebrates a decade of existence, because of the fact that it is the largest income transfer program in the country. We defend the maintenance of the program, through reforms in its structure and with the creation of complementary programs that enable the emancipation of poor individuals and overcoming their poverty.